Diabetes detrimental effects on enamel and dentine formation. Issue 5 (May 2015) - Abbassy, M.A.; Watari, I.; Bakry, A.S.; Hamba, H.; Hassan, Ali H.; Tagami, J.; Ono, T.
Abstract Objectives Understanding morphological changes and mineral content of tooth hard tissues may influence dental treatment. In this study, the effect of Type 1 Diabetes Mellitus (T1DM) on tooth structure was examined. Methods Experimental T1DM was induced in 3-week old male Wistar rats (n = 10) by a single dose of 60 mg/kg body weight of Streprozotocin. All rats were injected with calcein twice during the experiment and sacrificed at the age of 7 weeks old. Micro-computed tomography (micro-CT) was used to determine the mineral density and thickness of enamel and dentine. Also, a histomorphometery study was conducted to detect the rates of dentine mineral apposition and formation. The examined area was in the crown analogue of the rat mandibular incisor parallel to the long axis of the mesial surface of the first molar. All results were compared using Students' t-test (p < 0.05). Results Results showed that the enamel and dentine thickness were significantly reduced (hypoplasia) and there was a significant reduction of the rate of dentine mineral apposition and formation, while there was no significant effect of the T1DM condition on the mineral density of enamel and dentine. Conclusions T1DM has a detrimental influence on the formation of enamel and dentine in the early growth stage. Clinical significance T1DM condition may alter treatment planning of orthodontic treatment as it is associated with decreased enamel and dentin thickness that may affect teeth size and their resistance to caries.